2021
DOI: 10.1177/10547738211053507
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Antepartum Depression and Postpartum Depression on Exclusive Breastfeeding: A Systematic Review and Meta-Analysis

Abstract: The aim of this study was to systematically review the impact of antepartum depression on exclusive breastfeeding. A total of 15 studies were included in the review and 12 studies were used for the meta-analysis. The mean values of antepartum depression indicated that women who breastfed exclusively between 3 and 6 months had less antepartum depression symptoms (Mean Difference = −0.55, 95% CI = −0.76 to −0.35). The analysis also showed that the existence of antepartum depression was negatively related to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
(127 reference statements)
3
8
0
Order By: Relevance
“…[39][40][41] Systematic reviews have also found that postpartum depression and anxiety are associated with lower breastfeeding duration and exclusivity rates. [41][42][43] Overall, breastfeeding self-efficacy, anxiety, and depression were associated with a shorter duration of exclusive breastfeeding exclusive duration but not predictive, Further, research is warranted to examine the relationship between maternal mental health and infant feeding behaviours.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 95%
“…[39][40][41] Systematic reviews have also found that postpartum depression and anxiety are associated with lower breastfeeding duration and exclusivity rates. [41][42][43] Overall, breastfeeding self-efficacy, anxiety, and depression were associated with a shorter duration of exclusive breastfeeding exclusive duration but not predictive, Further, research is warranted to examine the relationship between maternal mental health and infant feeding behaviours.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 95%
“…Breastfeeding positively affects maternal mood and has been shown to reduce the stress response 21. The nonlactating mother is more likely to experience postpartum depression (PPD) (or vice versa), with exclusive breastfeeding correlating with lower likelihood of depressive symptoms 22-24. Especially when paired with limited social support and increased stress levels, the discontinuation of exclusive breastfeeding is associated with significantly higher odds of PPD 22.…”
Section: Breastfeedingmentioning
confidence: 99%
“…21 The nonlactating mother is more likely to experience postpartum depression (PPD) (or vice versa), with exclusive breastfeeding correlating with lower likelihood of depressive symptoms. [22][23][24] Especially when paired with limited social support and increased stress levels, the discontinuation of exclusive breastfeeding is associated with signifi cantly higher odds of PPD. 22 Longer duration of breastfeeding may promote maternal attachment, specifi cally maternal response to the infant, maternal sensitivity, and maternal ability to read the infant's cues.…”
Section: Health Benefi Ts For the Lactating Parentmentioning
confidence: 99%
“…For example, a recent meta-analysis linked parent mental health to child quality of life and another study found that parents with greater mental health concerns had children with poorer adherence to their medications (9,10). Parent mental health is also predictive of the earliest feeding interactions, including breastfeeding duration, as well as subsequent mealtime interactions when the child is older (11)(12)(13).…”
Section: What Is Newmentioning
confidence: 99%